Empowering families : the early intervention in natural environments professional development community of practice project in Ohio - Harjusola-Webb, Sanna; Gatmaitan, Michelle; Lyons, Ashley (Social Welfare: Interdisciplinary Approach, 2013)
This paper describes a model of professional development for Early Intervention based on an ongoing project taking place in a Midwestern state in the United States of America. The Project framework is presented as a model for high-quality professional development in Early Intervention by combining a) content including evidencebased practices and recommended practices from national professional organizations; b) university-community-family partnerships, an invaluable component without which the Project would not be possible; and c) tools for effective communication, collaboration, and coaching to support adult learning. As the Project is ongoing, research and program evaluation data are not reported in this paper. However, implications for young children and families, early intervention practitioners and stakeholders, and professional development in both the authors’ local context and the wider global context are discussed.
Keywords: early intervention; professional development; family empowerment